Translanguaging In Social Media : A Case Study Of Zhafira Aqila’s Youtube Channel - Amalia Rosyidah Misbah; Syamsudin Syamsudin (Journal of Research in Social Science and Humanities, 2024)
This study aims to investigates the use of translanguaging by Indonesian students who are continuing their education in the United States. The research was motivated by the rampant use of translanguaging, especially through the use of social media such as YouTube. The study examines forms of translanguaging, including code-switching (CS), code-mixing, and multimodal communication, as well as the functions these serve in shaping audience engagement. Through a qualitative descriptive analysis of three videos, the research identifies that code-switching is the most prominent component, appearing in 82% of "Grad School Decision Reaction," 80% of "Welcome Orientation at Harvard," and 70% of "Last Week of the Semester at Harvard." Translation and interpretation (TI) are more prevalent in academic videos, particularly in "Last Week of the Semester at Harvard" (30%) and "Welcome Orientation at Harvard" (18%), while less frequent (18%) in "Grad School Decision Reaction." Speech functions such as referential (RF) and metalinguistic (MF) are the most prominent, with MF accounting for 64% of speech functions across all videos, emphasizing Zhafira’s reflection on language use. This study emphasizes the significance of translanguaging as a key strategy for effective communication and identity expression in digital media, offering insights into how creators like Zhafira engage with multilingual audiences in today’s globalized environment.